Cardio-Renal Syndrome Type 4: The Correlation Between Cardiorenal Ultrasound Parameters - Silvia Lai; Mauro Ciccariello; Mira Dimko; Alessandro Galani; Silvio Lucci; Rosario Cianci; Amalia Mariotti (Karger Publishers, 2016)
Bakground/Aims: Cardiovascular diseases represent the leading causes of morbidity and mortality in patients with cronich kidney disease (CKD). The pathogenesis includes a complex, bidirectional interaction between heart and kidney termed cardiorenal syndrome type 4. The aim of study was to evaluate the association between renal and cardiovascular ultrasonographic parameters and identify early markers of cardiovascular risk. Methods: A total of 35 patients with CKD and 25 healthy controls, were enrolled and we have evaluated inflammatory indexes, mineral metabolism, renal function, renal and cardiovascular ultrasonographic parameters. Results: Tricuspid anular plane systolic excursion (TAPSE) and estimated pulmonary artery systolic pressure (ePAPs) showed a statistically significant difference between CKD patients and healthy controls (pConclusion: CKD can contribute to the development and progression of right ventricle dysfunction with endothelial dysfunction, inflammation and mineral metabolism disorders. Accurate assessment of right ventricular function is recommended in patients with CKD. RRI and echocardiographic parameters can be an important instrument for the diagnosis, prognosis and therapeutic assessment of cardio-renal syndrome in these patients.